2021
DOI: 10.1021/acs.jpclett.1c00855
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Exploration of Electrochemical Nitrate Reduction Reaction Activities on Transition-Metal-Doped h-BP

Abstract: Electrocatalytic conversion of nitrate (NO3 –) into ammonia can not only eliminate harmful pollutant but also provide a green method for a low-temperature ammonia synthesis. The electrochemical NO3 – reduction reactions (NO3RRs) of a series of transition-metal-doped hexagonal boron phosphide (h-BP) monolayers were comprehensively evaluated using density functional theory. The V-doped h-BP monolayer was found to stand near the top of the volcano plot with the limiting potential of −0.22 V versus a reversible hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 39 publications
7
57
0
Order By: Relevance
“…According to the previous reports, SACs are efficient for various types of electrochemical and photochemical reaction, such as the hydrogen evolution reaction (HER), 11 oxygen evolution reaction (OER), 12 oxygen reduction reaction (ORR), 13 CO 2 reduction reaction (CO 2 RR), 14,15 N 2 reduction reaction (NRR), [16][17][18] NO reduction reaction (NORR), 19,20 N 2 O reduction reaction (N 2 ORR), 21 and nitrate reduction reaction (N 3 ORR). 22,23 Various noble or non-noble atoms anchored on 2D substrates as NRR catalysts have been designed and explored both theoretically and experimentally. For example, Xue and co-workers theoretically investigated the NRR performance of Mo anchored on a C 9 N 4 monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous reports, SACs are efficient for various types of electrochemical and photochemical reaction, such as the hydrogen evolution reaction (HER), 11 oxygen evolution reaction (OER), 12 oxygen reduction reaction (ORR), 13 CO 2 reduction reaction (CO 2 RR), 14,15 N 2 reduction reaction (NRR), [16][17][18] NO reduction reaction (NORR), 19,20 N 2 O reduction reaction (N 2 ORR), 21 and nitrate reduction reaction (N 3 ORR). 22,23 Various noble or non-noble atoms anchored on 2D substrates as NRR catalysts have been designed and explored both theoretically and experimentally. For example, Xue and co-workers theoretically investigated the NRR performance of Mo anchored on a C 9 N 4 monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 So far, SACs have shown good catalytic performance for a variety of electrocatalytic systems, e.g. , water-splitting reaction, 16 N 2 O reduction, 17 NO 3 reduction, 18,19 oxygen reduction, 18,19 and N 2 20 and CO 2 reduction. 21 Substantially, H 2 O 2 is derived from the partial reduction of O 2 via the 2e − ORR process on the cathode, of which the side reactions are the 4e − ORR and the hydrogen evolution reaction (HER).…”
Section: Introductionmentioning
confidence: 99%
“…23,24 For instance, Jin et al reported that the N-doped carbon dry gel showed good ORR electrocatalytic activity and stability under acidic conditions. 18,19 Ma et al indicated that N-HCNPs carbon nanoparticles had better stability, methanol permeability resistance and CO toxicity resistance, as well as compatible catalytic activity to the Pt/C catalyst. 25 The porous C 6 N 6 material 26 synthesized by the solvothermal method, featuring a well-distributed hole and N-rich characteristic, exhibited the narrow-band semiconductor (band gap of 1.58 eV 27 ) and anchoring sites with respect to other CN systems (C 2 N, 28 α-C 2 N 2 , 29 β-C 2 N 2 , 29 g-C 3 N 4 , 30 C 4 N 31 and γ-C 4 N 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the one-step electrocatalytic upgrade of n-valeraldehyde to high-value-added octane has remained unexplored. In recent years, single-atom catalysts have been gradually utilized in the elimination of inorganic and organic pollutants, such as NO, [40] carbon monoxide, [41] carbon dioxide, [42] nitrate, [43,44] 1, 2-dichloroethane, [34] and upgrade of N 2 and 1, 2-dichloroethane, [34,45] and good results are obtained. Herein, we fabricate an Au SACs-NiMn 2 O 4 spinel synergetic composites via simple and feasible adsorption-deposition method and apply it in the one-step electrocatalytic upgrade of n-valeraldehyde to octane.…”
mentioning
confidence: 99%